THE INFECTION EFFECT OF STRAIN H37Rv MYCOBACTERIUM TUBERCULOSIS ON APOPTOSIS OF MICE’S NEURON CELL BRAIN (MUS MUSCULUS) - Kaspia, Rima Nor; Hidayati, Dwi Yuni Nur; Widayati, Aris (Malang Neurology Journal, 2016)
Background. Ischemia on the cells and the lack of supply of glucose, will trigger a Ca2 + influx into the cell and increased expression of glutamate. Result in mitochondrial Ca2 + Influx be